ANALISIS MAJAS PADA CERITA PENDEK â€œMATAHARI PUN TAK BOSANâ€ KARYA DANIL GUSRIANTO - Mega Asih; Indra Permana; Yeni Rostikawati (IKIP Siliwangi, 2021)
A short story or short story is a literary work that is dialectically related between reality and short stories, proving that from various angles short stories can be analyzed. This research was carried out because in the short story